1983
DOI: 10.1111/1523-1747.ep12534593
|View full text |Cite
|
Sign up to set email alerts
|

Proline Analogues Inhibit Human Skin Fibroblast Growth and Collagen Production in Culture

Abstract: Several structural analogues of proline have been shown to be incorporated into proteins in place of proline. As a consequence, the proliferation of cells in culture and the extracellular deposition of collagen in animal systems are reduced. In this study, the effects of two proline analogues, cis-4-hydroxy-L-proline and L-azetidine-2-carboxylic acid, on the growth parameters and procollagen production by cultured normal human skin fibroblasts were examined. The results indicated that incubation of the cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(34 citation statements)
references
References 31 publications
0
34
0
Order By: Relevance
“…CGC assays were performed in the presence of L-DHP, a proline analog that impairs the secretion of collagen 22 as a consequence of its inability to be hydroxylated by prolyl-4-hydroxylase. 23 Compared with controls lacking L-DHP, the contraction of collagen was inhibited significantly by L-DHP at concentrations of 1 to 2 mmol/L ( Figure 4B). Furthermore, cells in which collagen synthesis was inhibited lacked cellular projections and were not surrounded by collagenous bundles, resembling LXSN control cells (data not shown).…”
Section: Resultsmentioning
confidence: 91%
“…CGC assays were performed in the presence of L-DHP, a proline analog that impairs the secretion of collagen 22 as a consequence of its inability to be hydroxylated by prolyl-4-hydroxylase. 23 Compared with controls lacking L-DHP, the contraction of collagen was inhibited significantly by L-DHP at concentrations of 1 to 2 mmol/L ( Figure 4B). Furthermore, cells in which collagen synthesis was inhibited lacked cellular projections and were not surrounded by collagenous bundles, resembling LXSN control cells (data not shown).…”
Section: Resultsmentioning
confidence: 91%
“…The following amino acids were used at the indicated concentrations in 0.2% peptone: aspartic acid-monosodium salt (0.8 mM), threonine-free acid (0.3 mM), serine-free acid (0.5 mM), glutamic acid-monosodium salt (1.3 mM), proline-free acid (1.6 mM), glycine-HCl (4 mM), alanine-free acid (2 mM), cysteine-HCl (30 M), valinefree acid (40 M), methionine-free acid (0.2 mM), isoleucine-free acid (0.2 mM), leucine-free acid (0.5 mM), tyrosine-HCl (70 M), phenylalanine-free acid (0.2 mM), histidine-HCl (50 M), lysine-HCl (0.5 mM), arginine-HCl (0.6 mM), and tryptophan-free acid (30 M). To further investigate the role of proline in reversing aberrant Ras phenotypes, the following proline analogs (22) were tested; D-proline, 2-azetidinecarboxylic acid (AZC), thiazolidine-2-carboxylic acid, and thiazolidine-4-carboxylic acid (thioproline) (all from Sigma-Aldrich). All analogs were used at the same molar concentration (1.6 mM) used for proline.…”
Section: Methodsmentioning
confidence: 99%
“…Shortly after, Prockop's group also showed that cis-4-hydroxy-L-proline (CHLP) is incorporated into protocollagen and other proteins in place of L-proline and that the resulting unassembled or malfolded procollagen is not extruded into the extracellular matrix at a normal rate (Rosenbloom and Prockop, 1971;Uitto et al, 1975). An intracellular accumulation of polypeptides not folded into a stable triple-helical conformation was observed that is not tolerated by cells (Kao and Prockop, 1977;Tan et al, 1983). Recently, it was shown that the retention of procollagen within the endoplasmatic reticulum is mediated by prolyl 4-hydroxylase (Walmsley et al, 1999).…”
mentioning
confidence: 99%